Penerapan Enterprise Resource Planning pada UMKM JHN Shop Batam - Delfina Delfina (Universitas Borneo Tarakan, 2022)
Today's business competition forces many large companies and MSMEs think about strategies to survive in a competitive market. The JHN Shop MSMEs are no exception, which need to digitize their business strategies to achieve work efficiency. So that the service was carried out to assist Mr. A Ing in implementing the ERP system at JHN Shop to overcome all the problems faced and to help JHN Shop achieve work efficiency. The service method used is advocacy in the form of assistance through three stages, namely preparation, implementation and evaluation. Some of the data needed to launch mentoring activities was obtained through interviews with Mr A Ing. The results of the mentoring activities are in the form of knowledge and also the Odoo ERP system that can be used by Mr. A Ing in the long term to create work efficiency. After using Odoo ERP, you can see changes in the JHN Shop business processes that have been integrated between one division and another. The ERP also needs to be used consistently so that JHN Shop can feel the long-term impact that can bring JHN Shop to a competitive advantage